Improving Organizational Citizenship Behavior through Organizational Climate Development, Transformational Leadership and Self-Efficiency (Empirical Study Using Correlational Approach and SITOREM Analysis on State Senior High School Teachers in East Jakarta) - Ridwan, Ridwan; Abdullah, Thamrin; Sunaryo, Widodo (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
The purpose of this study is to find efforts to increase Organizational Citizenship Behavior in East Jakarta State Senior High Schools through the development of Organization Climate, Transformational Leadership and Self Efficacy. These efforts are made through the identification of the strengths between these variables. This research is a combination study using a correlational approach and SITOREM Analysis. Correlational statistical methods are used to determine whether Organization Climate, Transformational Leadership and Self Efficacy variables have a positive relationship with Organizational Citizenship Behavior. The SITOREM analysis is used to determine the order of priorities and the recommendations for improvement of the indicators needed. The results of a study of 39 East Jakarta State Senior High Schools showed that all variables were positively related to Organizational Citizenship Behavior. The results of the correlation strength sequence based on the highest correlation are Organization Climate ry1 = 0,653 (p<0,01), Self Efficacy ry3 = 0,620 (p<0,01) and Transformational Leadership ry2 = 0,544 (p<0,01). SITOREM Analysis Results show that the indicators that need improvement leadersjp and policy. The suggestion that can be conveyed is teachers must carry out organizational duties seriously and with high discipline. This is a form of teacher responsibility towards the profession that can increase organizational citizenship behavior